Effectiveness of Creative Dramatics Method on Academic Achievement, Learning Joyfulness and Creative Sense of Learners - Paleeri, Sankaranarayanan (JOURNAL OF INDIAN EDUCATION, 2021)
This paper examines the effectiveness of creative dramatics method on the achievement in social science, joyfulness in learning and creative sense. Observations cum opinion schedule for teachers, joyfulness inventory and achievement test in social Science for students were used as the tools. The study revealed that the creative dramatic method is effective to develop— (i) the achievement in social science, and (ii) learning joyfulness and creative sense among secondary level school students.